A Facile Strategy of Boosting Photothermal Conversion Efficiency through State Transformation for Cancer Therapy. Issue 51 (14th October 2021) - Li, Jie; Wang, Jianxing; Zhang, Jianyu; Han, Ting; Hu, Xiyao; Lee, Michelle M. S.; Wang, Dong; Tang, Ben Zhong
Abstract: Improving photothermal conversion efficiency (PCE) is critical to facilitate therapeutic performance during photothermal therapy (PTT). However, current strategies of prompting PCE always involve complex synthesis or modification of photothermal agents, thereby significantly inhibiting the practical applications and fundamental understanding of photothermal conversion. A facile strategy is herein present for boosting PCE by transforming photothermal agents from aggregated state to dispersed state. Compared to aggregated state, the developed photothermal agents with semiconducting nature can rotate freely in dispersed state, which allows for an efficient nonradiative dissipation through twisted intramolecular charge transfer (TICT) effect, consequentially offering excellent photothermal performance. Noteworthy, the state transformation can be achieved by virtue of releasing photothermal molecules from nanoparticles on the basis of a pH‐responsive polymer nanocarrier, and the PCE is elevated from 43% to 60% upon changing the pH values from 7.4 to 5.0. Moreover, the nanoparticle disassembly and state transformation behaviors can also smoothly proceed in lysosome of cancer cells, demonstrating a distinct photothermal therapeutic performance for cancer ablation. It is hoped that this strategy of transforming state to boost PCE would be a new platform for practical applications of PTT technique. Abstract : A facile strategy of improving photothermal conversion efficiency (PCE) is presented through transforming photothermal agents from aggregated to dispersed state, where the intramolecular motions are completely liberated, allowing for supra‐efficient heat generation. This state transformation can be achieved by virtue of a releasing process from nanoparticles in cancer cells, demonstrating a distinct photothermal therapeutic performance for cancer ablation.